CHARACTERIZATION OF METAL WORKING FLUIDS USING TRIBOLOGICAL TESTING METHODS - Ostrowicki, Nicolai; Markert, Johannes; Hanenkamp, Nico (MM Science Journal, 2021)
The objective of this paper is to determine whether it is possible to compare the lubricating properties of different Metal working fluids (MWF) for a defined cutting application using easily reproducible tribological tests. The idea is that this will eventually allow users of MWF to select the most suitable MWF for a specific application without the need to run expensive and time-consuming tests on a machine tool being unavailable for production during that time. The test method chosen is the Pin-on-Disc (PoD) test, as there has been extensive research and an easy setup can be acquired inexpensively, making it more available and attractive for potential users. The PoD-tests were done with two groups of MWF, those for wet machining and those for minimum quantity lubrication (MQL). Additionally, the viscosity of the MQL-MWF has been measured using a capillary viscometer. The evaluation of the wear on the pins and discs with different measuring devices shows consistent and promising results for the comparison of MQL-MWF, while the MWF for wet machining display only limited comparability with the PoD-setup used.
CRIS-Team WoS Importer:2021-11-26